Development of an electronic measuring device for body weight and nutritional status for children under two years old - Nasution, Naimah; Widyawati, Melyana Nurul; Ramlan, Djamaluddin (Universitas Muhammadiyah Purwokerto, 2022)
Background: Measurement of body weight and nutritional status in children under two years are still used manuals. Besides that, there is no tool to measure nutritional status, so it is necessary to develop a tool to make it easier.Purpose: The study aims to develop and test a measuring device for weight and nutritional status in children under two years.Methods: This study is Research and Development (R&D). It consisted of 5 stages, stage I (literature study), stage II (product development), stage III (expert validity and phase I trials), stage IV (product revision and final product), and stage V (phase II trials).Result: The electronic measuring device for weight and nutritional status has been created. The result is that the tool effectively determines the weight and nutritional status. The average value of tool testing is below 5%, which means the calibration value of the tool's sensitivity is valid in determining body weight. In addition, it can also determine nutritional status with a p=0,65, which means that there is no difference between measuring nutritional status using the tool and manually.Conclusion: The electronic measuring device effectively determines the weight and nutritional status.